Construction of the structural equation model of stigma, self-disclosure, social support, and quality of life of breast cancer patients after surgery—a multicenter study - Bu, Liuxiu; Chen, Xisui; Zheng, Shaoyan; Fan, Guanhua (Frontiers in Oncology, 2023)
Purpose: Stigma is common in patients with breast cancer after surgery, which has a negative impact on the quality of life(QOL). This study aimed to investigate the QOL of breast cancer patients after surgery and to analyze the multiple chains mediating effects of self-disclosure and social support between stigma and QOL. Methods: A total 292 patients of breast cancer patients after operation were recruited in this study. A questionnaire survey was conducted using the general information questionnaire, the consumer experiences of stigma questionnaire (CESQ), the distress disclosure index(DDI), the perceived social support scale(PSSS), and the functional assessment of cancer therapy-breast(FACT-B). Path analysis was conducted to test the hypothesized serial multiple mediation model. Results: The total scores of stigma, self-disclosure, social support and QOL were 15 (10 ~ 22), 39 (31 ~ 46), 58 (50 ~ 67) and 88 (74 ~ 104) respectively. QOL of breast cancer patients after the operation was negatively correlated with stigma (p < 0.01), and positively correlated with self-disclosure and social support (p < 0.01). Self-disclosure and social support played a complete mediating effect between stigma and QOL, and the total mediating effect value was 85. 87%. Conclusions: Self-disclosure and social support play a complete intermediary role between stigma and QOL. In order to improve the quality of life of patients, medical staff should pay attention to the assessment of stigma, encourage patients to express their emotions, and encourage their families and friends to respond to their expression and needs of patients.